2014
DOI: 10.5465/ambpp.2014.17478abstract
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of University-Level Support Policies on Female Participation in Academic Patenting

Abstract: A growing stream of academic literature investigates various factors which impede the participation of women in patenting and commercialization of the patented research; however, limited research has been performed on the ways to address this gender gap. We explore whether the institutional ownership arrangements of university patent, as well as the presence of such university-level support measures as a technology transfer office (TTO) and IP policy has a positive effect on the female involvement in patenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…For decades, scholars have pointed out gender disparities in science and its commercialisation (Larivière et al 2013;Jadidi et al 2018;Whittington and Smith-Doerr 2005). These disparities have been illustrated as a gender gap of entrepreneurship (Corley and Gaughan 2005;Besley et al 2018a;Sugimoto et al 2015) in terms of invention disclosure (Colyvas et al 2012), patenting (Whittington and Whittington 2011;Dohse et al 2017), consultation (Corley and Gaughan 2005), and spinoff creation (Martin et al 2015;Kochenkova et al 2015). However, prevalent approaches in this literature have somehow ignored important markers of stratification that greatly limit the comparison of two populations of academics with different characteristics (Marginson 2016;Lincoln et al 2012;Tartari and Salter 2015).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, scholars have pointed out gender disparities in science and its commercialisation (Larivière et al 2013;Jadidi et al 2018;Whittington and Smith-Doerr 2005). These disparities have been illustrated as a gender gap of entrepreneurship (Corley and Gaughan 2005;Besley et al 2018a;Sugimoto et al 2015) in terms of invention disclosure (Colyvas et al 2012), patenting (Whittington and Whittington 2011;Dohse et al 2017), consultation (Corley and Gaughan 2005), and spinoff creation (Martin et al 2015;Kochenkova et al 2015). However, prevalent approaches in this literature have somehow ignored important markers of stratification that greatly limit the comparison of two populations of academics with different characteristics (Marginson 2016;Lincoln et al 2012;Tartari and Salter 2015).…”
Section: 2mentioning
confidence: 99%
“…In regard to academic entrepreneurship, it is "neither swift nor easy" for female academics to commercialise their research (Sinell et al 2018). Several studies have shown that female academics may disclose fewer inventions to their universities (Colyvas et al 2012) and are less likely to patent (Whittington and Whittington 2011;Dohse et al 2017), to engage in industry consulting activities (Corley and Gaughan 2005;Besley et al 2018), and even to create spinoffs than their male counterparts (Martin et al 2015;Kochenkova et al 2015). These differences are unlikely to be related to biological characteristics but rather are notably attributed to socially constructed gender-based unique barriers in the female entrepreneurship path (Malmström et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Extant research has provided evidence that the contextual structures in which entrepreneurial activity is carried out are often inherently gender-biased. Gender bias has been documented in innovation systems (Lindberg et al, 2014), entrepreneurship and innovation policy (Petterson, 2007), as well as in the supporting infrastructure for entrepreneurship, such as incubators (Marlow and McAdam, 2012) and technology transfer offices (Kochenkova et al, 2015). The gender bias is possibly leading to under-exploitation of resources associated with women as sources of entrepreneurial opportunities.…”
Section: Gender Equality In Regional Entrepreneurial Ecosystems: the mentioning
confidence: 99%